2021
DOI: 10.12688/f1000research.53689.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge, attitudes and preventive practices towards COVID-19 in health care professionals in Lima, Peru

Abstract: Background: Nowadays, we are facing a disease caused by SARS-CoV-2, known globally as COVID-19, which is considered a threat to global health due to its high contagiousness and rapid spread. Methods: Analytical cross-sectional study in 302 health professionals. An online questionnaire consisting of questions about knowledge, attitudes and practices (KAP) towards COVID-19 was applied. Socio-demographic, occupational and comorbidities factors were explored. Simple and multiple logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A previous study in Mexico also reported similar results, indicating that the general population of that country performed an average of 13.5 preventive actions against COVID-19 from a range of 0 to 19 ( Sánchez-Arenas et al, 2021 ). In the Peruvian case, although there are no data on the frequency of preventive behaviors against COVID-19, a study with health professionals indicated that 31.5% presented high levels of preventive practices ( Rivera-Lozada et al, 2021 ). On the other hand, Uruguay was one of the countries with the lowest frequency of preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Mexico also reported similar results, indicating that the general population of that country performed an average of 13.5 preventive actions against COVID-19 from a range of 0 to 19 ( Sánchez-Arenas et al, 2021 ). In the Peruvian case, although there are no data on the frequency of preventive behaviors against COVID-19, a study with health professionals indicated that 31.5% presented high levels of preventive practices ( Rivera-Lozada et al, 2021 ). On the other hand, Uruguay was one of the countries with the lowest frequency of preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was noted that poor knowledge about COVID-19 and negative attitudes toward the disease were associated with inadequate preventive behaviors. 6 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Also, Rivera-Lozada et al, [ 19 ] reported that the aspects most affected by the COVID-19 pandemic among healthcare professionals were mental health and daily activities with a total of 37.4% ( n = 113) obtained scores above the 75th percentile, with a predominance of fear of becoming infected (49.7%), returning home and infecting the family (45%) and fearing of death from COVID 19 (49.7%) [ 20 ]. Having sufficient knowledge about the spread of the disease and the role of protective measures can reduce these fears and anxieties as research suggests that lack of knowledge can result in the overestimation of risks.…”
Section: Discussionmentioning
confidence: 99%